Rare Findings in Cleidocranial Dysplasia Caused by RUNX Mutation - Kalayci Yigin, Aysel; Duz, Mehmet Bugrahan; Seven, Mehmet (Global Medical Genetics, 2021)
Background Cleidocranial dysplasia (CCD, #MIM119600) is an autosomal-dominant skeletal dysplasia characterized by delayed closure of the cranial sutures, aplasia, or hypoplasia of the clavicles and dental abnormalities. These findings were accompanied by mobile and drooping shoulders, frontal and parietal bossing, hypertelorism, brachycephaly, short stature, supernumerary, and late erupting teeth. Radiographic studies can reveal involvement of multiple bones including skull, chest, pelvis, and limbs. CCD can be diagnosed with clinical and radiological evaluation and validated by molecular studies. Heterozygous loss of function RUNX2 gene, which plays an important role in osteogenesis and differentiation of precursor cells, causes CCD phenotype.Methods In this article, we reported five cases from three unrelated families with CCD phenotype. All exons and exonic–intronic boundary regions of RUNX2 gene from five patients were analyzed by polymerase chain reaction amplification and direct Sanger-sequencing.Results Our patients had classical CCD phenotype and we detected three different previously described mutations including c.1171C > T, IVS4 + 4delAAGT and c.676G > A. However, nail dysplasia has never been associated with these mutations. Our patients had varying degrees of nail dysplasia. Two of three mutations are related with Runt DNA-binding domain of RUNX2 protein in Wnt signaling and c.1171C > T had effect on proline/serine/threonine-rich (PST) domain. Recently, Wnt signaling pathway was presented as a key regulator of digit and nail differentiation. Our data suggest that RUNX2 gene may have an essential role on embryogenesis of nails, probably by protecting their integrity.
Keywords: cleidocranial dysplasia; RUNX mutation; Sanger sequencing; rare findings